Pengaruh Substitusi Tepung Daun Kelor pada Pembuatan Dimsum sebagai Sumber Gizi - Yulianti, Hesti; Nasution, Fachri Ibrahim; Rahman, Arief Fazlul; AR, Reiza Mutia; Prendika, Wimpy; Adiba, Iffadhiya Fathin (JTPG (Jurnal Teknologi Pertanian Gorontalo), 2025)
Moringa plants have high nutritional content, especially in the leaves, so they have benefits for human health. Various innovations in food processing technology utilize moringa not only as a vegetable but can be processed into various forms of processed food, one of which is dimsum. Dimsum based on moringa leaf flour is a new food product where moringa leaves have a role as fortification to fulfill nutrition in food. Based on the description, this study was conducted to determine the effect of moringa leaf flour substitution (5%, 10%, 15%) on the quality and sensory properties of dim sum. This study used a research design model used was an experimental with a completely randomized design (CRD) of one factor, namely the formulation of moringa leaf flour with 3 replications. The treatment in this study was the substitution of moringa leaf flour and tapioca flour with a formulation of 5%:95% (D132), 10%:90% (D231), and 15:85% (D213). The analysis included organoleptic testing with hedonic tests by 20 untrained panelists and proximate testing. The best sensory test results for 5% moringa leaf flour substitution had a significant effect on the sensory evaluation assessment of appearance 3,73 , flavor 3,45 , aroma 3,68 and texture 3,65. The proximate test results for 5% moringa leaf flour substitution obtained a protein value of 12.69%, fat 1.32%, ash content 1.2%, moisture content 66,11% and carbohydrate 18.68%